Testing of equipment for removing reinforced concrete pile caps - D. V. Furmanov; N. N. Klochko; T. A. Krasnobaev (Вестник СибАДИ)
Introduction. The article discusses the requirements for equipment for removing pile caps of reinforced concrete piles. The machines produced nowadays have excessive power and strength parameters which has been noted and proved experimentally.Materials and methods. Using a prototype of operational equipment on the different piles of different cross-section the force parameters of the working process, the character of development of cutting resistance forces in the cycle were investigated.Results. The stick-slip nature of cutting resistance forces and then a sharp drop of these forces on the whole area of theoscillogram indicates the brittle character of the pile fracture. It is also noted that the dependence of head shearing resistance forces on the height of the pile cap is linear. Technological and constructive features of the new equipment were investigated. High productivity of the machine as a whole was shown.Discussion and conclusion. Based on the results of the tests, the authors concluded that further work on the study of the working process of removal of reinforced concrete pile caps is reasonable.